1. Rozwiąz równania:
a) -5x-17=-9x+3
b) 2x-4+5x=x+2
c) 7x+2=5+3x+9

2. Rozwiąż równania:
a) (4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
b) -(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)

Uwaga! Każdy minus przed nawiasem zmienia znak na przeciwny!

Przykład:
7x+14=5x-22 /-5x
2x+14=-22 /-14
2x=-36 /:2
x=-18

Prosze o pomoc!
Dam najlepsze!

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-22T19:02:02+01:00
1)

a)
-5x-17=-9x+3 / + 5x
-17 = -4x + 3 / -3
-20 = -4x /:-4
5 = x

b)
2x-4+5x=x+2
7x - 4 = x + 2 /-x
6x - 4 = 2 / +4
6x = 6 /:6
x = 1

c)
7x+2=5+3x+9
7x + 2 = 3x + 14 /-3x
4x + 2 = 14 /-2
4x = 12 /:4
x = 3

2)
a)
(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
4x - 5 + x - 7 - 2x + 8 = -3x + 4 - x + 6
3x - 4 = -4x + 10 / + 4x
7x - 4 = 10 /+4
7x = 14 /:7
x = 2

b)
-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-4 + 2x - 2x - 4 = 3x - 1 + 2x - 5 - 7 + 3x
-8 = 8x -13 /+13
5 = 8x /:8
x = 0,625
2010-02-22T19:02:31+01:00
Zad.1 a)
-5x - 17 = -9x + 3
4x = 20
x = 5
b)
2x - 4 + 5x = x + 2
7x - 4 = x + 2
6x = 6
x = 1
c)
7x + 2 = 5 + 3x + 9
7x + 2 = 3x + 14
4x = 12
x = 3
Zad. 2
a) (4x - 5) + (x - 7) - (2x-8) = (-3x + 4) - (x - 6)
4x - 5 + x - 7 - 2x + 8 = -3x + 4 - x + 6
3x - 4 = -4x + 10
7x = 14
x = 2
b)
-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-4 + 2x - 2x - 4 = 3x - 1 + 2x - 5 - 7 + 3x
-8 = 8x - 13
8x = 5
x = 5/8
Za wszelki błędy przepraszam.